Bank Sampah Maju Lestari Menjadi Solusi Alternatif Pemberdayaan Pengelolaan Sampah Mandiri: Studi Kasus Trah Nuryo Setiko di Kalurahan Sendangtirto, Berbah, Sleman - Sulistiyani, Ambar Teguh; Dewi, Novi Paramitha; Arsifatika, Nabilla; Hanifah, Khalda; Sumartini; Maryamah, Siti; Sunyoto (Jurnal Pengabdian, Riset, Kreativitas, Inovasi, dan Teknologi Tepat Guna, 2025)
Waste has become a critical issue in the Special Region of Yogyakarta (DIY). The overcapacity of the Piyungan landfill (TPA) has triggered disruptions in waste management in Yogyakarta City, Sleman Regency, and Bantul Regency. Sleman was designated as an alternative landfill site utilizing Sultanate ground land. However, this initiative, including waste management through Village-Owned Enterprises (BUMKal), has not successfully changed the public's tendency to litter. Although Sendangtirto already has attention to the waste problem, it needs the active participation of the community. In response to this challenge, the Nuryo Setiko Clan established the Maju Lestari Waste Bank in 2022 to promote self-reliant waste management behavior through the empowerment of clan members. This study employed an action research method supported by participant observation, focusing on 90% of clan members residing in Sendangtirto Village. The study used a qualitative approach and Participatory Action Research method. The results show that the Maju Lestari Waste Bank successfully provides scheduled waste weighing services, transforms behavior from littering to waste sorting, attracts customers from both the clan and the general public, and increases income through waste savings. In conclusion, the Maju Lestari Waste Bank successfully established a waste bank institution, raised awareness, and provided an effective self-reliant solution for community-level waste management.